(untitled) (Palestine Technical College Journal for Research and Studies, 2020)
This study aimed to present a proposed perception to reduce child labor in Palestine according to some Arab experiences, and to identify the bodies responsible for implementing the perception and the implementation mechanism. The content analysis method and the comparative method was used for a number of studies that represent Arab experiences in reducing child labor. A total of (22) studies or experiments were reported, and this study reached the following results: (a) the legislative, executive and partner bodies are responsible for curbing the phenomenon of child labor; (b) the ministry of labor, the ministry of education and the ministry of social development are the executive bodies of the proposed scenario; (c) civil society institutions represent partner bodies in the visualization.